Intercomparison of dose enhancement ratio and secondary electron spectra for gold nanoparticles irradiated by X-rays calculated using multiple Monte Carlo simulation codes. (January 2020) - Li, W.B.; Belchior, A.; Beuve, M.; Chen, Y.Z.; Di Maria, S.; Friedland, W.; Gervais, B.; Heide, B.; Hocine, N.; Ipatov, A.; Klapproth, A.P.; Li, C.Y.; et al.
Highlights: EURADOS organized an inter-code intercomparison of dose enhancement of gold nanoparticles irradiated by kVp X-ray spectra. Variations and uncertainties of dose enhancement are observed by using multiple Monte Carlo codes. This study gives a reference range of dose enhancement in simulating gold nanoparticles irradiated by X-ray spectra. This intercomparison improved the simulation performances by identifying differences in settings, scoring and analysis. Further inter-code intercomparisons ensure a high quality of dose assessment for gold nanoparticle-assisted radiotherapy. Abstract: Purpose: Targeted radiation therapy has seen an increased interest in the past decade. In vitro and in vivo experiments showed enhanced radiation doses due to gold nanoparticles (GNPs) to tumors in mice and demonstrated a high potential for clinical application. However, finding a functionalized molecular formulation for actively targeting GNPs in tumor cells is challenging. Furthermore, the enhanced energy deposition by secondary electrons around GNPs, particularly by short-ranged Auger electrons is difficult to measure. Computational models, such as Monte Carlo (MC) radiation transport codes, have been used to estimate the physical quantities and effects of GNPs. However, as these codes differ from one to another, the reliability of physical and dosimetric quantities needs to be established at cellular and molecular levels, so that the subsequent biological effects can be assessed quantitatively. Methods: In this work, irradiation of single GNPs of 50 nm and 100 nm diameter by X-ray spectra generated by 50 and 100 peak kilovoltages was simulated for a defined geometry setup, by applying multiple MC codes in the EURADOS framework. Results: The mean dose enhancement ratio of the first 10 nm-thick water shell around a 100 nm GNP ranges from 400 for 100 kVp X-rays to 600 for 50 kVp X-rays with large uncertainty factors up to 2.3. Conclusions: It is concluded that the absolute dose enhancement effects have large uncertainties and need an inter-code intercomparison for a high quality assurance; relative properties may be a better measure until more experimental data is available to constrain the models.